NGOs, Foreign Aid, and Development in Nepal - Karkee, Rajendra; Comfort, Jude (Frontiers in Public Health, 2016)
The number of Non-governmental Organisations (NGOs) has grown significantly in low and middle income countries including Nepal since 1990s due to a range of factors. A total of 31,971 NGOs and 189 INGOs (International Non-government Organisations) have been registered in Nepal between 1977 and 2014 in various sectors including health, agriculture, poverty-alleviation, and good governance. Despite thousands of NGOs and significant amounts of aid, Nepal remains one of the least developed countries. The case of Nepal indicates that aid and donor support alone are not sufficient for sustained development.